Elevated temperatures diminish the effects of a highly resistant rice variety on the brown planthopper - Horgan, Finbarr G.; Arida, Arriza; Ardestani, Goli; Almazan, Maria Liberty P. (Springer, 2021)
This study compares the effects of temperature (constant at 15, 20, 25, 30 and 35 °C) on adult longevity, oviposition, and nymph development of the brown planthopper, Nilaparvata lugens, on susceptible and resistant rice varieties. The resistant variety contained the BPH32 gene. In our experiments, nymphs failed to develop to adults at 15, 20 and 35 °C on either variety. Host resistance had its greatest effect in reducing adult survival at 20–25 °C and its greatest effect in reducing nymph weight gain at 25 °C. This corresponded with optimal temperatures for adult survival (20–25 °C) and nymph development (25–30 °C). At 25 and 30 °C, adult females achieved up to three oviposition cycles on the susceptible variety, but only one cycle on the resistant variety. Maximum egg-laying occurred at 30 °C due to larger numbers of egg batches produced during the first oviposition cycle on both the susceptible and resistant varieties, and larger batches during the second and third oviposition cycles on the susceptible variety; however, resistance had its greatest effect in reducing fecundity at 25 °C. This revealed a mismatch between the optimal temperatures for resistance and for egg production in immigrating females. Increasing global temperatures could reduce the effectiveness of anti-herbivore resistance in rice and other crops where such mismatches occur.